Robust optimal output voltage tracking algorithm for interleaved N-phase DC/DC boost converter with performance recovery property - Kim, Seok Kyoon; Park, Jin Hyuk; Lee, Kyo Beum (International Journal of Electronics, 2018)
This article suggests a cascade output voltage regulation algorithm for an N-phase interleaved DC/DC boost converter based on reference dynamics. The proposed algorithm has two advantages. The first is to guarantee the performance recovery property using the reference dynamics in the presence of a model-plant mismatch, and the second is to present a systematic procedure determining the stabilising control gains by solving an optimisation problem. The closed-loop performance of the proposed method is evaluated through simulations and experiments using a 3-kW four-phase interleaved DC/DC boost converter where the proposed method is compared with the feedback linearising method.
Keywords: BOOST converter; Closed-loop performance; Control gains; Four-phase; Optimisation problems; Output voltage regulation; Output voltages; Performance recovery; Interleaved DC/DC boost converter; performance recovery; reference dynamics; robust control